2022
DOI: 10.1007/s13346-022-01248-w
|View full text |Cite
|
Sign up to set email alerts
|

Boronates as hydrogen peroxide–reactive warheads in the design of detection probes, prodrugs, and nanomedicines used in tumors and other diseases

Abstract: Hydrogen peroxide (H 2 O 2 ) has always been a topic of great interests attributed to its vital role in biological process. H 2 O 2 is known as a major reactive oxygen species (ROS) which involves in numerous physiological processes such as cell proliferation, signal transduction, differentiation, and even pathogenesis. A plenty of diseases development such as chronic disease, in ammatory disease, and organ dysfunction are found to be relevant to abnormality of H 2 O 2 production. Thus, imminent and feasible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Conversely, ROS production is indeed an evident consequence of the increased respiration process, and exaggerated proliferation featuring cancer cells can be usefully exploited as a stimulus for the activation process within tumor tissue. Thus, a ROS-activated platinum (IV) prodrug bearing two boronate-ester-masked N-alkylaminoferrocene ligands has been proposed (Figure 17) [57]. Different studies have revealed that compound 50 can be selectively activated only by ROS, which is to both GSH and ascorbic acid stimuli.…”
Section: Treatment Of Cisplatin-resistant Tumor: Pt (Iv) Complexesmentioning
confidence: 99%
“…Conversely, ROS production is indeed an evident consequence of the increased respiration process, and exaggerated proliferation featuring cancer cells can be usefully exploited as a stimulus for the activation process within tumor tissue. Thus, a ROS-activated platinum (IV) prodrug bearing two boronate-ester-masked N-alkylaminoferrocene ligands has been proposed (Figure 17) [57]. Different studies have revealed that compound 50 can be selectively activated only by ROS, which is to both GSH and ascorbic acid stimuli.…”
Section: Treatment Of Cisplatin-resistant Tumor: Pt (Iv) Complexesmentioning
confidence: 99%
“…12,24,33 The latter can undergo hydrolysis or can react with glutathione (GSH) present in the cytosol, producing 4hydroxybenzyl alcohol (4-HBA) or a GSH-QM adduct, respectively. 34 Because GSH has an important role as an intracellular antioxidant, the GSH-QM adduct formed can deplete intracellular reserves of GSH and weaken the cell's antioxidative abilities. This depletion leads to an elevation of oxidative stress and increased ROS generation, with the consequent death of cancer cells due to their vulnerability to further ROS-associated toxicity.…”
Section: Account Synlettmentioning
confidence: 99%
“…Accumulating evidence indicates that hydrogen peroxide (H 2 O 2 ) is crucial in cancer initiation and progression . An arylboronate (BA)-based prodrug structure can selectively react with H 2 O 2 and release the active drug and quinone methide (QM) . This study introduced BA-linked doxorubicin (BA-DOX, Figure ) into our H 2 O 2 -stimulated prodrug model. , BA-DOX can react with H 2 O 2 , resulting in the insertion of oxygen atoms between the B–C bonds.…”
Section: Introductionmentioning
confidence: 99%